Implementation of Formic Acid as a Liquid Organic Hydrogen Carrier (LOHC): Techno-Economic Analysis and Life Cycle Assessment of Formic Acid Produced via CO2 Utilization - Kim, Changsoo; Lee, Younggeun; Kim, Kyeongsu; Lee, Ung (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
To meet the global climate goals agreed upon regarding the Paris Agreement, governments and institutions around the world are investigating various technologies to reduce carbon emissions and achieve a net-negative energy system. To this end, integrated solutions that incorporate carbon utilization processes, as well as promote the transition of the fossil fuel-based energy system to carbon-free systems, such as the hydrogen economy, are required. One of the possible pathways is to utilize CO2 as the base chemical for producing a liquid organic hydrogen carrier (LOHC), using CO2 as a mediating chemical for delivering H-2 to the site of usage since gaseous and liquid H-2 retain transportation and storage problems. Formic acid is a probable candidate considering its high volumetric H-2 capacity and low toxicity. While previous studies have shown that formic acid is less competitive as an LOHC candidate compared to other chemicals, such as methanol or toluene, the results were based on out-of-date process schemes. Recently, advances have been made in the formic acid production and dehydrogenation processes, and an analysis regarding the recent process configurations could deem formic acid as a feasible option for LOHC. In this study, the potential for using formic acid as an LOHC is evaluated, with respect to the state-of-the-art formic acid production schemes, including the use of heterogeneous catalysts during thermocatalytic and electrochemical formic acid production from CO2. Assuming a hydrogen distribution system using formic acid as the LOHC, each of the production, transportation, dehydrogenation, and CO2 recycle sections are separately modeled and evaluated by means of techno-economic analysis (TEA) and life cycle assessment (LCA). Realistic scenarios for hydrogen distribution are established considering the different transportation and CO2 recovery options; then, the separate scenarios are compared to the results of a liquefied hydrogen distribution scenario. TEA results showed that, while the LOHC system incorporating the thermocatalytic CO2 hydrogenation to formic acid is more expensive than liquefied H-2 distribution, the electrochemical CO2 reduction to formic acid system reduces the H-2 distribution cost by 12%. Breakdown of the cost compositions revealed that reduction of steam usage for thermocatalytic processes in the future can make the LOHC system based on thermocatalytic CO2 hydrogenation to formic acid to be competitive with liquefied H-2 distribution if the production cost could be reduced by 23% and 32%, according to the dehydrogenation mode selected. Using formic acid as a LOHC was shown to be less competitive compared to liquefied H-2 delivery in terms of LCA, but producing formic acid via electrochemical CO2 reduction was shown to retain the lowest global warming potential among the considered options.